MOTIF BATIK CIREUNDEU SEBAGAI MODEL PENCIPTAAN DESAIN TIPOGRAFI VERNAKULAR - Nur Fatimah Juliani, - (2020)
Nur Fatimah Juliani. 1602447. "CIREUNDEU BATIK MOTIF AS A MODEL FOR THE CREATION OF VERNACULAR TYPOGRAPHIC DESIGN". Thesis creation, Bandung: Fine Arts Education Study Program, Faculty of Arts Education and Design, University of Indonesian Education. The development of batik is a feature of the progress of Indonesian culture today. The symbolic meaning found in the Cireundeu batik motif is taken from the local history and culture, making it a visual identity of Cimahi City. Through vernacular typographic design, Cireundeu batik was developed with the aim of reintroducing through different media application. Formulation of creation problems, namely: 1) What are the ideas/concepts of using Cireundeu Batik motifs in the creation of vernacular typography? 2) What is the form of visualization? 3) How is the vernacular typography analysis of Cireundeu Batik visualization ?. The result of this creation aims to know the ideas/concepts, the visualization form of vernacular typography, as well as the results of the final analysis of the visual form. The creation method consists of data analysis, identification of material tools and the creation process including the stages of sketching, tracing and digitization. The end result of the creation of this vernacular typographic design consists of a set of Uppercase, Lowercase, Numeric and Symbol serif characters with Regular, Bold, Italic and Italic Bold letter specifications. The shape of the serif was chosen because it has a greater chance of being able to be modified decoratively. The main element of the letter builder is the line with the shape of the curve pattern, following the grid of the initial letter is the circle. The dominance of the form lies in the modification of the design of the stem / stem. This vernacular typographic design has a high level of readability, so it is suitable for use as a display type with a relatively large size. The result of this creation is expected to be an insight to preserve the local batik culture, especially the city of Cimahi. Keywords : Batik Cireundeu, Vernacular Typographic, Decorative, Display Type.